Application of Decision Support System in E-commerce - Narayanasamy, Kogilah; Velmurugan, M. Senthi (IBIMA Publishing, 2008)
Electronic commerce (EC) has the potential to improve efficiency and productivity in business activities. E-commerce today is no longer technological issue, but is also a business issue. A decision support system (DSS) is "an interactive information system that provides information, models and data manipulation tools to help make decisions in semi-structured and unstructured situations. E-commerce involves a number of forms, varying level of cost and complexity, depending on business need. This conceptual paper presents the e-commerce application by integrating with Decision support systems. It further highlights some critical issues in e-commerce, suggestion future strategies for e-commerce in years to come.